Performance analysis of selected Malaysian banks. - Goh, Ai Tin. (2013)
Singapore Airlines has undergone continuous upgrading over the last few decades. In view of the recent increase in the intensity of competition in the airline industry, it is timely to examine the corporate strategies of Singapore Airlines and the factors contributing to its competitive advantage.